2016
DOI: 10.1186/s12966-016-0448-9
|View full text |Cite
|
Sign up to set email alerts
|

Walkability and walking for transport: characterizing the built environment using space syntax

Abstract: BackgroundNeighborhood walkability has been shown to be associated with walking behavior. However, the availability of geographical data necessary to construct it remains a limitation. Building on the concept of space syntax, we propose an alternative walkability index, space syntax walkability (SSW). This study examined associations of the full walkability index and SSW with walking for transport (WT).MethodsData were collected in 2003–2004 from 2544 adults living in 154 Census Collection Districts (CCD) in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 31 publications
2
71
0
6
Order By: Relevance
“…-The relationship between human-made environments and walkability was studied with respect to the theory of space syntax and by using questionnaires. It was concluded that these two indicators had a positive correlation with one another [87,88]. Walkability in the environment was analyzed using GIS method and with respect to the 4 criteria, namely functional diversity, population density, business density and intersection density.…”
Section: Methodsmentioning
confidence: 99%
“…-The relationship between human-made environments and walkability was studied with respect to the theory of space syntax and by using questionnaires. It was concluded that these two indicators had a positive correlation with one another [87,88]. Walkability in the environment was analyzed using GIS method and with respect to the 4 criteria, namely functional diversity, population density, business density and intersection density.…”
Section: Methodsmentioning
confidence: 99%
“…A presença de estudos que correlacionam desenho urbano com transporte é bastante forte, sendo base para os seguintes assuntos: (1) relação entre as características do espaço físico e o uso de transportes não motorizados, (2) tratamento de áreas próximas às estações de transporte (DOT) e (7) soluções de desenho urbano para vagas de estacionamento. O tema mais recorrente (1) aponta, em sua maioria, a contribuição da densidade, do uso misto e da conectividade das vias para cidades com maior fluxo de pedestres, e de meios de deslocamento não motorizados, como a caminhada e a bicicleta (Boulange et al, 2017;Lee et al, 2017;Gunn et al, 2017;Lee, 2015;Lerman & Omer, 2016;Koohsari et al, 2016;Choi, 2014;Johnson & Marko, 2008;Krizek, 2003;Greenwald, 2003;Handy et al, 2002). Dentro dessa temática, há ainda artigos que trazem perspectivas complementares sobre a afirmação predominante.…”
Section: Desenho Urbano E Qualidade Dos Espaços Públicosunclassified
“…Nas propostas referentes ao uso e à ocupação do solo, por exemplo, a composição de conjuntos urbanos que superem exclusivamente o lote como unidade de referência de configuração urbana, o estabelecimento de limites mínimos e máximos de área construída computável destinada a estacionamento de veículos, ou mesmo a possibilidade de o passeio ganhar mais largura em compensação à dispensa de recuo frontal das edificações no lote têm clara sintonia com alguns dos artigos selecionados na terceira etapa da pesquisa. Uma das diretrizes que se tornou mais conhecida, a fachada ativa, está justamente associada a uma melhor relação entre a edificação, o seu uso lindeiro e a circulação de pedestres, mecanismo esse que se coloca em meio a um certo debate em torno da tese Jane Jacobs, na defesa do uso misto e da densidade como promotor de caminhabilidade, conceito defendido também por artigos descobertos pela pesquisa (Boulange et al, 2017;Lee et al, 2017;Gunn et al, 2017;Lee, 2015;Lerman & Omer, 2016;Koohsari, et al, 2016;Choi, 2014;Johnson & Marko, 2008;Krizek, 2003;Greenwald, 2003;Handy et al, 2002), ou, ao contrário, a crítica de que o uso misto e as maiores densidades populacionais geram a caminhabilidade, ao serem apontadas limitações nessa relação (Maat et al, 2005;Kemperman & Timmermans, 2009;Lee, 2015).…”
Section: Discussão E Considerações Finaisunclassified
See 1 more Smart Citation
“…Another study concluded that considering both residential density and the walkable destinations creates good measures of urban walkability and can be recommended for use by policy-makers, planners and public health officials [45]. However, an additional study suggested the Space Syntax Walkability (SSW) method, which employs gross population density and a space syntax measure of street integration, could provide a toolset for further understanding of how urban design makes an impact on walking behaviors [46]. The authors argued that, compared to conventional walkability measures, the SSW method appears to be an effective alternative to full walkability in terms of data availability and processing.…”
Section: Introductionmentioning
confidence: 99%